Pengaruh model Problem Based Learning (PBL) berbantuan media Flipbook terhadap kemampuan berpikir kritis siswa dalam pembelajaran IPA di Kelas V SDN Jatimulya 2 - Reghina Nurul Aghnia; Ejen Jenal Mutaqin; Widdy Sukma Nugraha (Universitas Sebelas Maret, 2025)
The development of technology and the challenges of the 21st century demand critical thinking skills; however, PISA results indicate low levels of this ability among Indonesian students, particularly in abstract science learning. This study aims to analyze the effect of the Problem Based Learning (PBL) model assisted by flipbook media on the critical thinking skills of fifth-grade students at SDN Jatimulya 2 in ecosystem learning. The method used is a pre- experimental design with a One-Group Pretest-Posttest approach, involving 21 students and data collection through critical thinking ability tests. The pretest results showed an average critical thinking ability of 45.12, while the posttest significantly increased to 75.21. The N-Gain analysis of 0.56 is categorized as